Visualizing the Anthropocene from Above. (May 2022) - Schrank, Zach
We created the Indiana Anthropocene project not only because we reside in this state, but also in order to demonstrate the scope and process of the new epoch in a familiar and defined location. This aerial photography project captures features of the Anthropocene within a regional bounded space, thus collapsing the global into the local. In other words, it provides a visual conceptualization of the geography we live in as a microcosm of the global stage. Furthermore, aerial drone photographs provide vantage points and perspectives of our world that can enhance our perception of society. It allows us to see and connect large-scale processes that otherwise remain hidden from the ground. Images from the sky piece together a complex visual socio-ecological story of how we interact with the environment on immense landscapes.